2016
DOI: 10.4103/1596-3519.172556
|View full text |Cite|
|
Sign up to set email alerts
|

Nurses' knowledge of care of chest drain: A survey in a Nigerian semiurban university hospital

Abstract: Background/Objective:Inefficient nursing care of chest drains may associated with unacceptable and sometimes life-threatening complications. This report aims to ascertain the level of knowledge of care of chest drains among nurses working in wards in a teaching hospital in Nigeria.Methods:A cross-sectional study among nurses at teaching hospital using pretested self-administered questionnaires.Results:The majority were respondents aged between 31 and 40 years (45.4%) and those who have nursing experience betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 13 publications
(20 reference statements)
3
25
1
2
Order By: Relevance
“…Most respondents in this study indicated that dressings would be changed when no longer functional, which is consistent with previous studies in the UK (Parkin, 2002), the Republic of Ireland (Lehwaldt & Timmins, 2005;Magner et al, 2013), Nigeria (Kesieme et al, 2016) and Turkey (Tarhan et al, 2016). Approximately half of respondents indicated that they would change chest-tube dressings routinely, and the frequency of changing dressings varied ranging from daily, every 2 days, every 3 days, every 3-4 days, every 3-7 days or weekly.…”
Section: When Should the Dressing Be Changed?supporting
confidence: 91%
See 2 more Smart Citations
“…Most respondents in this study indicated that dressings would be changed when no longer functional, which is consistent with previous studies in the UK (Parkin, 2002), the Republic of Ireland (Lehwaldt & Timmins, 2005;Magner et al, 2013), Nigeria (Kesieme et al, 2016) and Turkey (Tarhan et al, 2016). Approximately half of respondents indicated that they would change chest-tube dressings routinely, and the frequency of changing dressings varied ranging from daily, every 2 days, every 3 days, every 3-4 days, every 3-7 days or weekly.…”
Section: When Should the Dressing Be Changed?supporting
confidence: 91%
“…Most respondents indicated that to prevent chest-drainage tubes from becoming blocked, they would routinely manipulate (strip or milk) chest tubes, which was inconsistent with previous studies in the Republic of Ireland in 2013 (Magner et al, 2013), North America (Shalli et al, 2009) and the UK (Parkin, 2002) but closer to previous studies in the Republic of Ireland in 2005 (Lehwaldt & Timmins, 2005), Turkey (Tarhan et al, 2016) and Nigeria (Kesieme et al, 2016). Most respondents also thought that it was necessary to manipulate chest tubes to remove clots when clots impeded unobstructed drainage, which is inconsistent with recommendations from relevant systematic reviews (Charnock & Evans, 2001;Wallen et al, 2002) and a clinical evidence review (Halm, 2007) that drainage-tube manipulation should not be performed due to possible tissue damage and lack of demonstrable benefit.…”
Section: Should the Chest Drain Tubing Be Manipulated?contrasting
confidence: 72%
See 1 more Smart Citation
“…No study investigated such failure mode. Valencia et al and Kesieme et al found airway suctioning critical [28,29]. Suctioning may reduce airway resistance.…”
Section: Ventilator Malfunction 80mentioning
confidence: 96%
“…One of the causes of this clinical error was the lack of awareness to understand the importance of drainage system care. Based on Kesieme et al nurses' knowledge of the care of chest drain is poor and they require education in this area [29].…”
Section: Ventilator Malfunction 80mentioning
confidence: 99%